THE NGABUNGBANG TRADITION AS A FORM OF SOCIAL IDENTITY IN CIMANDE VILLAGE COMMUNITY - Dini Rahmawati; Haryono Haryono; Nurul Hayat (Sekolah Tinggi Keguruan dan Ilmu Pendidikan (STKIP) Melawi, 2025)
This research aims to gain a deeper understanding of the Ngabungbang Tradition as a Form of Social Identity in the Cimande Village Community, utilizing Clifford Geertz's Interpretive Anthropology perspective. The research approach employed in this study is qualitative with a descriptive method. For informant selection, a purposive sampling technique was utilized. Thefindings indicate that the history of the Ngabungbang tradition in Cimande Village initially originated from napak tilas (following in the footsteps/pilgrimage) or gatherings of teachers and students who sought to learn pencak silat. Over time, other rituals evolved, such as mapag mulud (welcoming the Prophet's birthday month), keuceran (washing of sacred heirlooms), bathing in Cikamalayan, and pilgrimages to the tombs of the revered elders. Based on these developments, this tradition has become an integral part of the Cimande Village community's social identity, with its peak event routinely held every 14th of Rabi' al-Awwal, the month of Prophet Muhammad's birth. The symbols present in this tradition consist of cai (water), bathing, prayer, heirlooms, and the tombs of the elders. Social interactions within this tradition occur among people from various backgrounds, such as the gathering of students who once learned silat in Cimande. The overall meaning of the Ngabungbang tradition in Cimande Village is to purify oneself by discarding negative aspects with the intention of repenting to Allah SWT. Keywords : Cultural Ritual, Ngabungbang Tradition, Social Identity